HUBUNGAN ORIENTASI TUJUAN DENGAN MOTIVASI BELAJAR SANTRI DI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH - M.Syakur; Nuraini (Fakultas Dakwah Universitas Ibrahimy, 2024)
Career decision making is a thinking process in selecting and determining various existingIslamic boarding schools are places where students gain and practice knowledge. Being in an Islamic boarding school requires students to have motivation to learn. One of the factors related to motivation is having a goal orientation. The aim of this research is to statistically test the relationship between goal orientation and students’ learning motivation in Islamic boarding schools. This research uses quantitative research methods with a correlation research type. The results of this research show that the level of goal orientation of students is in the high category as many as 49 students (56%), and as many as 38 students (44%) are in the medium category. The results of the level of student motivation to learn were in the high category as many as 58 students (67%) and as many as 29 students (33%) were in the medium category. The results of the product moment analysis show that there is a positive and very significant relationship between goal orientation and learning motivation as shown by the Pearson correlation results of (r) = 0.424 with sig (p) = 0.000 (p<0.05). The results of the analysis test show that the higher the level of goal orientation, the higher the learning motivation.